Studies on the antidiarrhoeal activity of Aegle marmelos unripe fruit: Validating its traditional usage - Antia Noshir; Tetali Pundarikakshudu; Daswani Poonam; Brijesh S; Birdi Tannaz (BMC, 2009)
Abstract Background Aegle marmelos (L.) Correa has been widely used in indigenous systems of Indian medicine due to its various medicinal properties. However, despite its traditional usage as an anti-diarrhoeal there is limited information regarding its mode of action in infectious forms of diarrhoea. Hence, we evaluated the hot aqueous extract (decoction) of dried unripe fruit pulp of A. marmelos for its antimicrobial activity and effect on various aspects of pathogenicity of infectious diarrhoea. Methods The decoction was assessed for its antibacterial, antigiardial and antirotaviral activities. The effect of the decoction on adherence of enteropathogenic Escherichia coli and invasion of enteroinvasive E. coli and Shigella flexneri to HEp-2 cells were assessed as a measure of its effect on colonization. The effect of the decoction on production of E. coli heat labile toxin (LT) and cholera toxin (CT) and their binding to ganglioside monosialic acid receptor (GM1) were assessed by GM1-enzyme linked immuno sorbent assay whereas its effect on production and action of E. coli heat stable toxin (ST) was assessed by suckling mouse assay. Results The decoction showed cidal activity against Giardia and rotavirus whereas viability of none of the six bacterial strains tested was affected. It significantly reduced bacterial adherence to and invasion of HEp-2 cells. The extract also affected production of CT and binding of both LT and CT to GM1. However, it had no effect on ST. Conclusion The decoction of the unripe fruit pulp of A. marmelos, despite having limited antimicrobial activity, affected the bacterial colonization to gut epithelium and production and action of certain enterotoxins. These observations suggest the varied possible modes of action of A. marmelos in infectious forms of diarrhoea thereby validating its mention in the ancient Indian texts and continued use by local communities for the treatment of diarrhoeal diseases.